Identification of patient subgroups with unfavorable long‐term outcomes associated with laparoscopic surgery in a randomized controlled trial comparing open and laparoscopic surgery for colon cancer (Japan Clinical Oncology Group Study JCOG0404). Issue 6 (9th August 2021) - Saito, Shuji; Akagi, Tomonori; Katayama, Hiroshi; Wakabayashi, Masashi; Inomata, Masafumi; Yamamoto, Seiichiro; Ito, Masaaki; Kinugasa, Yusuke; Egi, Hiroyuki; Munakata, Yasuhiro; Kokuba, Yukihito; Bando, Hiroyuki; et al.
Abstract: Background: Previously, we conducted a randomized controlled trial (JCOG0404) for stage II/III colon cancer patients and reported that the long‐term survival after open surgery (OP) and laparoscopic surgery (LAP) were almost identical; however, JCOG0404 suggested that survival of patients after LAP with tumors located in the rectosigmoid colon, cT4 or cN2 tumors, and high body mass index (BMI) might be unfavorable. Aim: To identify the patient subgroups associated with poor long‐term survival in the LAP arm compared with the OP arm. Methods: Patients aged 20–75, clinical T3 or deeper lesion without involvement of other organs, clinical N0‐2 and M0 were included. The patients with pathological stage IV and R2 resection were excluded from the current analysis. In each subgroup, the hazard ratio for LAP (vs. OP) in overall survival (OS) from surgery was estimated using a multivariable Cox regression model adjusted for the clinical and pathological factors. Results: In total, 1025 patients (OP, 511 and LAP, 514) were included in the current analysis. Adjusted hazards ratios for OS of patients with high BMI (>25 kg/m 2 ), pT4, and pN2 in LAP were 3.37 (95% confidence interval [CI], 1.24–9.19), 1.33 (0.73–2.41), and 1.74 (0.76–3.97), respectively. In contrast, that of rectosigmoid colon tumors was 0.98 (0.46–2.09). Conclusions: Although LAP is an acceptable optional treatment for stage II/III colon cancer, the present subgroup analysis suggests that high BMI (>25 kg/m 2 ), pT4, and pN2 except for RS were factors associated with unfavorable long‐term outcomes of LAP in patients with colon cancer who underwent curative resection. (JCOG 0404: NCT00147134/UMIN‐CTR: C000000105.) Abstract : CONSORT diagram. OP, open surgery; LAP, laparoscopic surgery. Of the 1057 patients, the patients with pathological stage IV and R2 resection were excluded. The final number of patients analyzed was 1025.